French mental health first aid guidelines for eating disorders: an exploration of user characteristics and usefulness among college students. Issue 2 (31st August 2016) - Melioli, Tiffany; Rispal, Magali; Hart, Laura M.; Chabrol, Henri; Rodgers, Rachel F.
Abstract: Aim: The literature has highlighted that strategies to increase appropriate and timely treatment seeking for eating disorders (EDs) are needed. The aim of this study was to use the Internet to disseminate guidelines for providing first aid to individuals suffering from ED among college students. Methods: Users were invited to complete two surveys: an initial one assessing user characteristics and, 28 days later, a questionnaire assessing the perceived usefulness of the guidelines. A sample of 651 college students ( M age  = 22, standard deviation (SD) = 3.9) responded to the first questionnaire and 50 completed the second questionnaire ( M age  = 22.2, SD = 2.6). Results: The guidelines were downloaded 1174 times and 56% of users reported finding them useful. Conclusions: College students might be particularly interested in learning more about ED and the guidelines could be valuable to address the gap in available resources for ED‐related mental health literacy.